Prediabetes Screening with American Diabetes Association (ADA) Scoring in the Primary Health Care Yogyakarta (Development And Validation Of Scoring Systems) - Yaltafit Abror Jeem; Hari Koesnanto; Muhammad Robikhul Ikhsan (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2020)
Background: Numerous studies have shown  the increasing of prediabetes incidence from the time being. Some of the prediabetes screening methods that can be performed at primary health care were American Diabetes Association (ADA) scoring for prediabetes. However, there was no data that describes the validity and applicability of the ADA scoring on prediabetes patients in Indonesia. Objective: To discribe prediabetes screening and to find out the applicability of the ADA scoring method in Yogyakarta primary health care. Method: The diagnostic test by scoring system of the ADA questionnaire was compared with OGTT (oral glucose tolerance test) as the gold standard. The subjects were patients of primary health care in Yogyakarta who fulfill the inclusion and exclusion criteria. Result: The subjects were 279 respondents with 227 female  (81.4%) and 52 male patients (18.6%). The mean age of the study subjects was 50.4 years (SD 12.81). The sensitivity and specificity of the scoring method of ADA was 61% and 71%. This could be influenced by the difference in BMI standard as one of the scoring items. Conclusion: Prediabetes prevalence was 11.1% in the study population. The sensitivity and specificity of the scoring method of ADA is 61% and 71%. The scoring method of ADA could not be used in primary health care.